A Scholarly Knowledge Graph-Powered Dashboard: Implementation and User Evaluation - Lezhnina, Olga; Kismihók, Gábor; Prinz, Manuel; Stocker, Markus; Auer, Sören (Frontiers in Research Metrics and Analytics, 2022)
Scholarly knowledge graphs provide researchers with a novel modality of information retrieval, and their wider use in academia is beneficial for digitalisation of published works and development of scholarly communication. To increase the acceptance of scholarly knowledge graphs, we present a dashboard, which visualises research contributions on an educational science topic in the frame of the Open Research Knowledge Graph (ORKG). As dashboards are created at the intersection of computer science, graphic design, and human-technology interaction, we used these three perspectives to develop a multi-relational visualization tool aimed at improving the user experience. According to preliminary results of the user evaluation survey, the dashboard was perceived as more appealing than the baseline ORKG-powered interface. Our findings can be used for development of scholarly knowledge graph-powered dashboards in different domains, thus facilitating the acceptance of these novel instruments by research communities and increasing versatility in scholarly communication.